2020
DOI: 10.3233/blc-190258
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Urothelial Carcinoma: Response to Chemotherapy and Oncologic Outcomes

Abstract: BACKGROUND: Plasmacytoid urothelial carcinoma is a rare bladder cancer variant with scarce data on outcomes and prognostic factors. OBJECTIVE: We report our institutional experience with this histology to determine response to neoadjuvant chemotherapy, definitive surgery and survival. METHODS: We conducted a retrospective chart review of consecutive patients with plasmacytoid, as well as conventional urothelial carcinoma (for comparison) seen in our institution (2007-2018). Baseline characteristics, clinicopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…However, chemotherapy, which has been historically used for conventional or pure urothelial cancers, has often been used with relatively good success in PVUC, although the durability of response is often lacking [6]. However, a few reports have shown inconsistent benefit from the use of neoadjuvant or adjuvant chemotherapy [16][17][18], often used whenever possible, followed by consolidative surgery as the main therapeutic option of choice. In a retrospective study of 31 patients with PVUC, pathological down-staging was found in 80% of patients with resectable disease compared to the upstaging found in most patients who received surgery up-front.…”
Section: Discussionmentioning
confidence: 99%
“…However, chemotherapy, which has been historically used for conventional or pure urothelial cancers, has often been used with relatively good success in PVUC, although the durability of response is often lacking [6]. However, a few reports have shown inconsistent benefit from the use of neoadjuvant or adjuvant chemotherapy [16][17][18], often used whenever possible, followed by consolidative surgery as the main therapeutic option of choice. In a retrospective study of 31 patients with PVUC, pathological down-staging was found in 80% of patients with resectable disease compared to the upstaging found in most patients who received surgery up-front.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in CDH1 are pathognomonic of PUC and result in the loss of E-cadherin expression in its tumour cells, this is thought to explain the higher rates of tumour cell migration observed [34,35].…”
Section: Modern Approach To Diagnosis and Treatment Of Bladder Cancermentioning
confidence: 99%
“…Urachal adenocarcinoma is covered in a separate review by the CUA and GUMOC [197]. Supporting evidence for OS benefit of NAC is limited or has conflicting results in micropapillary [198][199][200][201][202], plasmacytoid [203][204][205][206][207][208], nested [209,210], and sarcomatoid variants [177,[211][212][213], thus recommendations cannot be made in these settings at this time. Local definitive therapy may be the most important component of curative therapy.…”
Section: Variant Histologymentioning
confidence: 99%